GEMABAKTI II: Edukasi Ekoliterasi melalui Pembuatan Produk Ecobrick di UPT SPF SMP Negeri 28 Makassar, Pulau Barrang Lompo - Syamsul; Syahriani; Maulana, Akram Caesar; Mufliha, Nur; Ramadhani, Sri Riska (Faculty of Tarbiyah and Teacher Training, 2026)
Plastic waste problems in island communities require not only technical handling but also educational intervention. GEMABAKTI II aimed to provide ecoliteracy education through waste sorting and hands-on ecobrick production. The activity was conducted on 17 July 2023 at UPT SPF SMP Negeri 28 Makassar, Barrang Lompo Island, involving 190 students from grades VII–IX. The program comprised preliminary coordination, education on plastic-waste impacts, waste sorting, demonstration and product-making practice, and process evaluation based on participant engagement and product completion. All groups completed the sorting and plastic-compaction stages and produced three product types: a waste bin made from used bottles, an ecobrick bench, and an ecobrick table. The activity offered contextual learning that connected knowledge of plastic waste with simple waste-management action. As no pretest–posttest or standardized ecoliteracy instrument was administered, the findings represent process and product achievements rather than quantitative evidence of increased ecoliteracy. Program sustainability requires teacher mentoring, routine waste sorting, and measurable evaluation in subsequent activities.